Theory and practice of formation of electronic document circulation in public institutions of the Russian Federation (on the example of the Southern Customs Administration) ("Journal "U". Economy. Management. Finance.", 2019)
The article discusses the advantages and disadvantages of the introduction of electronic document management system in the state institution – the southern customs administration. This innovation undoubtedly affects the efficiency of each of the staff and the organization as a whole, which is an important factor in the functioning of the organization. In addition to the technology of implementation, the consequences of such a decision are analyzed, which are not only positive, but also negative.
Keywords: office work, electronic document management system, document, customs management, document management